Calculus

posted by .

How do you do this question.
f(x) = (5x-1)/(2-3x), find f^(-1)(x). The answer is supposed to be (1+2x)/(5+3x).
--------------------------------------
And can you please explain this one to me.
Suppose that xy^(3)+2y^(2)+xy+2x^(3) = 0. Find the general expression for dy/dx. Also, find the value of dy/dx at the point where x = 1.
I have no idea how to differentiate that.

Thanks so much for the help!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    suppose x S f(t) dt= x^2 - 2x + 1. Find f(x). 1 S = integral and 1 = lower level, x = upper i don't understand what i'm supposed to find/what to do
  2. algebra

    how do i verify a question when i am solving for Y.. yet i need to subsatoute X first to find Y. such as in this probelm to find Y ((xy)/(x+4)-(2y/x)=3 solve for Y i end up with........lets say that X=4 Y= (3x^2+12x)/(x^2-2x+8) Y=6 …
  3. Calculus - Damon

    Find the line which passes through the point (0, 1/4) and is tangent to the curve y=x^3 at some point. So I found the derivative which is 3x^2. Let (a, a3) be the point of tangency. 3x^2 = (a3 - 1/4)/(a-0) I'm not sure how to solve …
  4. pre calculus

    Question 1: Explain why the equation of the line y=5 has a slope that is undefined. Explain in words or mathematically. Question 2: Given any circle, the coordinates of one endpoint of a diameter is (3,-2). If the coordinates of the …
  5. calculus

    Suppose f(x) is the function 2x^3+ 12x^2+ 21x + 3. Find the smallest value of f at which the tangent to the curve is 3. I did: f'(x)+ 6x^2+ 24x + 21= 3 = 6(x+3)(x+1), x= -3, -1 the correct answer is supposed to be -8
  6. calculus

    Please help with this very complicated question! Using 3(x-3)(x^2-6x+23)^1/2, as the chain rule fifferentiation of f(x)=(x^2-6x+23). Please explain how I find the general solution to dy/dx= 2/27(x-3)SQUARE ROOT BEGINS (x^2-6x+23)/y …
  7. calculus

    I posted this below, and no one answered. Please help with this very complicated question! Using 3(x-3)(x^2-6x+23)^1/2, as the chain rule differentiation of f(x)=(x^2-6x+23). Please explain how I find the general solution to the differential …
  8. calculus

    I posted this below, and no one answered. Please help with this very complicated question! Using 3(x-3)(x^2-6x+23)^1/2, as the chain rule differentiation of f(x)=(x^2-6x+23). Please explain how I find the general solution to the differential …
  9. Calculus II

    Fed loves polynomials with rational coefficients and only such polynomials.Suppose f(x)=square root of x. Find a polynomial P(x) that Fred will adore so that, for any x in the interval [3,5], the difference between P(x) and f(x) is …
  10. Pre-Calculus

    Solve the equation 2x + 5y - 3z = -1. Write the general solution as a matrix equation. [x] [ ] [1] [y]= [ ] X [s] [z] [ ] [t] I'm supposed to fill in that blank in the middle, but I don't understand how to solve this if I'm only given …

More Similar Questions